1979
DOI: 10.1007/bf02272799
|View full text |Cite
|
Sign up to set email alerts
|

Teenage pregnancy and perinatal mortality

Abstract: In the general population teenage pregnancies present an elevated rate of perinatal mortality compared with pregnancies of women in their 20s. In 2 large-scale university hopsital studies (American and Danish) the teenage pregnancies showed lower perinatal mortality than those of any other age group. This article attempts to determine the origin of these differing results. A comparative analysis was conducted, focusing on methodologies, subject characteristics, and treatment procedures involved in the 2 cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…These results confirm previously published data that showed young marital age as the underlying cause of poor pregnancy outcome 5 –8 . Moreover, they produced insights on the cumulative impact of maternal marital age on the entire childbearing period, which could be the possible reason for studies that failed to detect the relationship between young maternal age and single pregnancy outcome 9 –15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm previously published data that showed young marital age as the underlying cause of poor pregnancy outcome 5 –8 . Moreover, they produced insights on the cumulative impact of maternal marital age on the entire childbearing period, which could be the possible reason for studies that failed to detect the relationship between young maternal age and single pregnancy outcome 9 –15 …”
Section: Discussionmentioning
confidence: 99%
“…In the Arab world, the situation is different as early maternal marriage is encouraged by the families, early childbearing is a means to confirm fertility of the newly married couple and the newborn is mostly welcomed by members of the whole family 4 . Moreover, extensive studies that have been performed in developed countries to outline the role of young maternal age on maternal and infant health have been directed at the first pregnancy and its outcome 5 –15 . Our knowledge of the cumulative effect of biologically immature bodies engaged early in the process of pregnancy and delivery on subsequent maternal and infant health during the childbearing period, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between mother's age and neonatal outcomes is generally described as being J shaped (Chamberlain et al, 1975), reflecting an elevated level of problems among offspring of teenagers and progressively more problems for women over age 30. In contradiction to this, B. R. Mednick, Baker, and Sutton-Smith (1979) analyzed the above-noted Danish sample and found the relationship between maternal age and pregnancy outcome to approximate linearity, that is, the younger the mother, the lower the rate of perinatal mortality and complications. Analyses of the white subsample from the American Collaborative Study yielded findings similar to those of the Danish perinatal study in that no indication was found of higher levels of problems among teenagers even within the youngest group below 15 years of age.…”
Section: Influences On Neonatal Statusmentioning
confidence: 94%
“…Analyses of the white subsample from the American Collaborative Study yielded findings similar to those of the Danish perinatal study in that no indication was found of higher levels of problems among teenagers even within the youngest group below 15 years of age. Based on these findings, B. R. Mednick et al (1979) suggested that the negative effect of teenage pregnancy on neonatal outcomes is mostly a function of the fact that many young pregnant women either do not seek or do not have access to adequate medical care. The conclusion that adequate medical care alone will do away with the increase in nonoptimal pregnancy outcomes among very young or economically and/or socially disadvantaged women needs at least one qualification: The social milieu may be so oppressive that increased medical care may not totally eliminate its negative effects.…”
Section: Influences On Neonatal Statusmentioning
confidence: 99%
“…Generalizations based on data reported by Baldwin 1982aBaldwin , 1982bBaldwin and Cain, 1980;Bolton, 1980;Card and Wise, 1978;Furstenberg, 1971;Kellam, et al, 1982;Mednick et al, 1979;Menken, 1980;Moore and Burt, 1982;Nye and Lamberts, 1980. The negative consequences of adolescent pregnancy are unfortunate, but might be tolerable without major intervention, if they were not widespread. Unfortunately, there have been more than a million teenage pregnancies each year for several years {Alan Guttmacher Institute, 1981}.…”
mentioning
confidence: 97%